Parks and recreation. Season seven, the farewell season [videorecording (DVD)] - Daniels, Greg; Schur, Michael, 1975- (Universal Studios Home Entertainment, 2015)
Say goodbye to Leslie Knope, the world's most dedicated government employee. The year is 2017, and Leslie's life has changed dramatically: she's now the mother of triplets and works for the National Parks Department, but, most shockingly, has become sworn enemies with her former friend and mentor, Ron Swanson. Join Leslie's final acts of determination (and sometimes desperation) to make Pawnee, "the greatest town in America," even better.